Introduction to the Special Issue on Human Dignity, Religion, and Rights in Contemporary China. Issue 5 (4th July 2019) - Mauldin, Joshua T.
ABSTRACT: This introductory essay to a special issue on "Human Dignity, Religion, and Rights in Contemporary China" provides background material for readers unfamiliar with debates over religion and politics in China today. Political theology in China raises many questions that western readers will find familiar, but the Chinese context often requires different answers, so that gaining familiarity with the Chinese discussion can broaden our view of the available options at the intersection of religion and politics. At the same time, seeing familiar questions from a Chinese perspective can illuminate implicit disagreements within the western context that would otherwise remain hidden. This special issue brings together theologians, ethicists, sociologists, and legal scholars around fundamental questions of political order in a rapidly changing society.